Manifiesto Creación (2022)
Recognize creation as a journey in life; being so we cannot ignore our single presence in space. Everything is affected in time and space from the most seemingly insignificant. For example: the place that we occupy inside a store, square, social group, will always be affected by our presence, even if it is only arrange to remain silent.